2023
DOI: 10.1002/ldr.4662
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prediction of land use changes and population dynamics in the Gorganrud River basin, Iran

Abstract: Analyzing land use/land cover change is a fundamental tool for evaluating the environmental consequences of human activities. This research was conducted to detect and predict likely land use changes in the Gorganrud River basin, Iran, and to estimate past and future population growth as a driving force in land use change and degradation. First, land use maps for 1999, 2009, and 2017 were prepared. Then, the likely land use changes for 2030 and 2040 were predicted using the Land Change Modeler (LCM) in TERRSET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Another study in Saudi Arabia, which utilized the LCM MLP-NN algorithm to predict LULC for 2040, resulted in an overall accuracy of 88% (Alqadhi et al, 2021). The other research conducted by Ghonchepour et al (2023) in the Gorganrud River basin, Iran, obtained higher validation results for the 2040 LULC map and correlated with the predicted population as a main driving force in such changes. They further concluded that other driver variables should be considered to identify the driving forces behind such a transition so that effective management strategies can be utilized.…”
Section: Comparison With Similar Studies and Validationmentioning
confidence: 94%
“…Another study in Saudi Arabia, which utilized the LCM MLP-NN algorithm to predict LULC for 2040, resulted in an overall accuracy of 88% (Alqadhi et al, 2021). The other research conducted by Ghonchepour et al (2023) in the Gorganrud River basin, Iran, obtained higher validation results for the 2040 LULC map and correlated with the predicted population as a main driving force in such changes. They further concluded that other driver variables should be considered to identify the driving forces behind such a transition so that effective management strategies can be utilized.…”
Section: Comparison With Similar Studies and Validationmentioning
confidence: 94%
“…Written by Kilburn KH, Thornton JC and Hanscom B. In this paper, researchers argue that brain function testing is conceptually similar to lung function testing..The authors used these tests to evaluate 293 adults from three unexposed groups in different regions of the United States..Subjects were contacted randomly from the voter registration rolls and compensated for their time..The tests included balance, reaction time, strength, hearing, visual performance and cognitive recall, perceptual motor and memory functions..The regression equations simulate the performance of each test and the effect of demographic factors..The resulting prediction equations will help researchers conduct quantitative tests on chemically exposed individuals and others with brain damage [3].…”
Section: Introductionmentioning
confidence: 99%